Endangered bivalves as antimicrobial-resistant Escherichia coli and other species of the Enterobacteriaceae family. - Saavedra, Maria José (2022)
Freshwater unionoids are one of the most threatened animal groups worldwide, suffering dramatic regressions globally. The freshwater pearl mussel Margaritifera margaritifera, currently listed as critically endangered in Europe, and Potomida littoralis, listed as endangered, are both present in the River Tua basin (Portugal). These aquatic long-lived organisms, responsible for important functions and vital ecosystem services [1], are sensitive to environmental changes, making them excellent bioindicators [2]. According to Grizzle & Brunner [3] mussels are capable of establishing symbiotic mutualistic or antagonistic relationships with bacteria. The inappropriate use of antibiotics has led to the emergence and spread of resistant bacteria, recognized today as a serious public health problem. Based in the concept of “One health”, the objective of this study was to examine the antibacterial resistance rates in Escherichia coli and other Enterobacteriaceae isolates obtained from water and the two freshwater bivalve species collected in the River Tua Basin.